A single-institution retrospective analysis of gastric carcinoma with positive peritoneal lavage cytology and without serosal invasion: A case series. (March 2019) - Sakata, Taizo; Takahata, Takaomi; Kimura, Toshikazu; Yasuhara, Isao; Kojima, Toru; Akazai, Yoshihiro; Mimura, Tetsushige; Lefor, Alan Kawarai
Abstract: Background and objectives: Peritoneal dissemination of gastric cancer is often associated with serosal infiltration. The aim of this study was to evaluate the clinical importance of peritoneal lavage cytology in patients with gastric carcinoma without serosal invasion. The incidence and impact on prognosis of positive cytology were analyzed. Methods: Of 2768 patients with gastric cancer, outcomes and pathological characteristics of 973 patients were reviewed retrospectively. All patients underwent peritoneal lavage at laparotomy for curative or palliative resection of gastric cancer between 1999 and 2017. Among these, 479 who underwent surgery from January 1999 to March 2012 were also reviewed to analyze 5-year survival. Results: Of 973 patients enrolled, 338 (35%) did not have serosal invasion, and peritoneal cytology was positive in 4/338 (1.2%). Of these four patients, one had submucosal invasion and three had muscularis propria invasion. Of 635 patients with serosal invasion, peritoneal cytology was positive in 74/635 (12%). Of 479 patients reviewed for survival, cytology was positive in 32/479, with 3/32 (9%) surviving for five years, and cytology was negative in 447 patients with 266/447 (60%) surviving for five years. Conclusions: Cytologic evaluation should be routinely performed in patients with early-stage gastric cancer. Highlights: Patients with gastric carcinoma without serosal invasion can have positive cytology, although cytologic evaluation has a relatively low sensitivity. Positive cytology is associated with a significantly worse prognosis. Lymph node metastases and distant metastasis were significant risk factors for positive peritoneal cytology.